Phasing out DEHP from plastic indwelling medical devices used for intensive care: Does it reduce the long-term attention deficit of critically ill children? - Vanhorebeek, Ilse; Malarvannan, Govindan; Güiza, Fabian; Poma, Giulia; Derese, Inge; Wouters, Pieter J.; Joosten, Koen; Verbruggen, Sascha; Jorens, Philippe G.; Covaci, Adrian; Van den Berghe, Greet (Environment international, 2022)
[Display omitted] •Exposure of critically ill children to DEHP in the PICU decreased over the years.•Reduced DEHP exposure in the PICU did not result in improved long-term attention.•Whether alternative plasticizers are neurodevelopmentally safe remains unclear. Children who have been critically ill face long-term developmental impairments. Iatrogenic exposure to di(2-ethylhexyl)phthalate (DEHP), a plasticizer leaching from plastic indwelling medical devices used in the pediatric intensive care unit (PICU), has been associated with the pronounced attention deficit observed in children 4 years after critical illness. As concerns about DEHP toxicity increased, governmental authorities urged the phase out of DEHP in indwelling medical devices and replacement with alternative plasticizers. We hypothesized that exposure to DEHP decreased over the years, attenuating the pronounced long-term attention deficit of these vulnerable children. We compared plasma concentrations of 3 oxidative DEHP metabolites (5cx-MEPP, 5OH-MEHP, 5oxo-MEHP) on the last PICU day in 216 patients who participated in the Tight Glucose Control study (2004–2007) and 334 patients who participated in the PEPaNIC study (2012–2015) and survived PICU stay. Corresponding minimal exposures to these metabolites (plasma concentration multiplied with number of days in PICU) were also evaluated. In patients with 4-year follow-up data, we compared measures of attention (standardized reaction times and consistency). Comparisons were performed with univariable analyses and multivariable linear regression analyses adjusted for baseline risk factors. In the PEPaNIC patients, last PICU day plasma concentrations of 5cx-MEPP, 5OH-MEHP, 5oxo-MEHP and their sum, and corresponding minimal exposures, were reduced to 17–69% of those in the Tight Glucose Control study (p < 0.0001). Differences remained significant after multivariable adjustment (p ≤ 0.001). PEPaNIC patients did not show better attention than patients in the Tight Glucose Control study, also not after multivariable adjustment for risk factors. Exposure of critically ill children to DEHP in the PICU decreased over the years, but the lower exposure did not translate into improved attention 4 years later. Whether the residual exposure may still be toxic or whether the plasticizers replacing DEHP may not be safe for neurodevelopment needs further investigation.